MODIFIED SWITCHING CHARACTERISTICS OF CARBON NANOTUBES BLENDED WITH TYPE II CdTe QUANTUM DOTS - A WATTS,; M GREEN,; A WAHEED,; S.K. CHAKARVARTI,; M FARMER, (International Journal of Pharma and Bio Sciences, 2014)
We have investigated the electrical properties of the hetero structures deposited on conductive glass. The hetero structures made with type II CdTe quantum dots present interesting peculiarities. Low frequency (20Hz ≤ f≤ 200kHz; f= 8804) dielectric properties of type II CdTe, type II CdTe blended with Single-wall carbon nano tubes SWNTs functionalized with poly (ethylene glycol ) hetero junctions, were investigated in details at room temperature. Negative capacitance was observed at low frequencies under forward dc biases. . By using frequency dependent capacitance spectroscopy, the tunnelling effects of holes and electrons were investigated. Peaks were observed In capacitance curves measured at low frequency, which could be attributed to the resonant tunnelling of charge carries into discrete energy levels of nanocrystalline CdTe and exhibit quantum confinement and coulomb blockade effects. A clear (positive/negative) shift in capacitance-voltage(C-V) and conductance-voltage (G-V) suggests (electron/hole) trapping in nanocrystalline quantum dots.